Design of 8 Bit Microcontroller - Singh, Inderjeet (My University, 2008)
One of the important aspects of modern electronic technology is embedded systems based on microcontrollers. Microcontrollers are such an important part of this digital word where everyone wants to complete ones intended task in as minimum time as possible. So this Thesis work is devoted for the design and implementation of 8-bit Microcontroller RISC Architecture and then optimizing it for high speed and low power. Presented Microcontroller RISC have instruction set of 23 instructions and each instruction is executes in a single cycle including branch instructions which is an enhancement to the previously version of the RISC. The presented Microcontroller RISC is optimized to operate at high speed and dissipates low power and operates at 1.4 Volt power supply. Power managed mode has been added in this microcontroller to reduce power. In Power managed mode the microcontroller enters idle mode. The source of motivation for the designed Architecture is architecture is PIC16F84A microcontroller, which is available commercially but operates at 5 volts power supply. In this thesis work, Microcontroller RISC is designed in Verilog HDL and functional simulation is done in Xilinx.
M.Tech
Keywords: RISC; Power Managed Mode; Microcontroller